2019
DOI: 10.3390/agriculture9050088
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Validity of Animal-Based Indicators of Sheep Health and Welfare: Do Observers Agree?

Abstract: Sixteen animal-based indicators of sheep welfare, previously selected by a stakeholder panel, and based on the Farm Animal Welfare Council (FAWC) Five Freedoms, were assessed in terms of the level of inter-observer agreement achieved during on-farm testing. Eight observers independently tested the 16 indicators on 1158 sheep from 38 farms in England and Wales. Overall inter-observer agreement was evaluated by Fleiss’s kappa (κ), and the pair-wise agreement of each observer was compared to a ‘test standard’ obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Body condition score, together with the farming system, was confirmed to be one of the most important driving factors for the efficiency performance of our sample, as it is widely regarded as a fundamental animal-based welfare indicator (Richmond et al 2017;Phythian et al 2019). It is conceivable to expect that optimal BCS scores, which are associated with better animal welfare, have a positive influence on animal health status, productive/reproductive performance and farm efficiency.…”
Section: Discussionmentioning
confidence: 65%
“…Body condition score, together with the farming system, was confirmed to be one of the most important driving factors for the efficiency performance of our sample, as it is widely regarded as a fundamental animal-based welfare indicator (Richmond et al 2017;Phythian et al 2019). It is conceivable to expect that optimal BCS scores, which are associated with better animal welfare, have a positive influence on animal health status, productive/reproductive performance and farm efficiency.…”
Section: Discussionmentioning
confidence: 65%
“…They are listed and discussed below from the most frequently cited to the least. Further 23 indicators were cited only once [23][24][25][26][27][28][29][30][31][32]. Thus, the amount of information is too small to judge the value of these indicators in terms of a general applicability.…”
Section: Single Indicatorsmentioning
confidence: 99%
“…Categorizing animals as "obviously sick" would allow an overall impression [23], as sheep suffering from welfare issues can be recognised through their dull, depressed demeanour [6,26]. Conducting this kind of observations, in sheep or in lambs, has proven to be feasible on-farm as the animals do not need to be gathered or handled [26,32] and showed a promising level of intra-and inter-observer reliability [24,32].…”
Section: Behaviour Assessmentmentioning
confidence: 99%
“…Indeed, supernumerary teat removal correlates with a reduced incidence of subclinical mastitis in Dutch dairy heifers, although this observation could point to wider management differences between farms implementing different removal policies, rather than necessarily reflecting a direct effect (Santman‐Berends et al ). In small ruminants, as in cattle, bacterial mastitis is a major health issue with welfare implications (Hughes & Watson, ), in both dairy sheep (Bramis et al ) and those used for meat production (Phythian et al ; Crump et al ; Phythian et al ). It has been suggested that poor udder conformation, including the presence of supernumerary teats, may also constitute a minor, but notable, risk factor for acquisition of new intramammary infections (Vasileiou et al ), potentially as an indirect effect due to impairment of lamb sucking and consequent inefficient removal of milk (Menzies & Ramanoon, ).…”
Section: Introductionmentioning
confidence: 99%